Atuação docente na sala de recursos multifuncionais da rede municipal de Macapá/AP - Alves, Helen Cristiane Viana (2018)
The Specialized Educational Assistance is a right established in the Federal Constitution to all students with disabilities, being offered in the Multifunctional Resource Rooms that provide access to services and pedagogical resources and accessibility in schools of the regular network of education. To do so, it is necessary for the schools to provide adequate space for their installation, as well as a specialized teacher for ESA. The present study had as general objective to characterize the teaching performance in multifunctional resource rooms (SRM) of schools of the municipal teaching network of Macapá. Specific objectives were: a) to identify the public that receives specialized educational services in SRMs; b) know the operating conditions and referrals of students to SRMs; c) identify how the teacher organizes his / her teaching work, and d) verify what the teachers think about the school inclusion and implications in the teaching performance. It consisted of a research of qualitative character with exploratory-descriptive character and was realized in Schools of the municipal public network of education in Macapá; having as participants, six (6) teachers who worked in the Specialized Educational Assistance. The schools where the teachers interviewed worked were located in different areas of the city of Macapá, distributed between the North, South, East and West zones, totaling two (2) schools in the South zone, two (2) in the North zone, one ) in the West zone and one (1) in the East zone. The data collection was done through the application of an interview to the teachers who were selected through a lottery. The analyzed data were organized in thematic axes based on the information obtained in the interviews. The results revealed that ESA teachers have a positive conception about inclusion. It was found that a part of multifunctional resource rooms does not have all the necessary resources to attend students, and when they have resources such as games, equipment and computers, they do not work. Students are referred to the specialized educational service by the school secretary and in some situations, the Municipal Education Department, through the Special Education Division, conducts this referral. Participants indicated that the planning of student attendance is done, mostly in partnership with teachers in the regular classroom. As a result, it was also observed that teachers attend a very diversified clientele, which requires adequate training that addresses the demands demanded by the process of school inclusion and that foster student learning, which requires a proposal from the public sector training for these professionals. The data showed the importance of the support of families, the bodies responsible for special education and the school as a whole. It is hoped that this research can contribute with the scientific knowledge and that encourages future works that come to discuss about the Special Education in the municipality of Macapá